Optical and acoustical phonon modes in superlattices with SiGe QDs - Yukhymchuk, V.O.; Dzhagan, V.M.; Klad’ko, V.P.; Lytvyn, O.S.; Machulin, V.F.; Valakh, M.Ya.; Yaremko, A.M.; Milekhin, A.G.; Krasil’nik, Z.F.; Novikov, A.V.; Mestres, N.; Pascual, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Multilayers with SiGe nanoislands grown in a broad temperature range (300-600 °C) are studied using Raman spectroscopy, HRXRD and AFM. It is shown that the islands are fully strained when obtained at 300 °C and gradually relax with the growth temperature increase. The main contribution to the Raman peaks caused by scattering on folded acoustic phonons in multilayers (n ≤ 10) with nanoislands is due to the islands themselves. The enhancement of the scattering intensity due to resonance of the exciting light with the electronic transitions inside the islands is shown to play a significant role.